Antecedents of Packaging of Product and Its Effect on Customer’s Perception towards the Use of Perfumes - SAQIB SHAHZAD; SHAHZAD KHAN; DR. SHAHID JAN; MUHAMMAD TUFAIL (Journal of Business & Tourism, 2021)
The purpose of the study was to find out the antecedents of packaging of product and its impact on customer’s perception towards the purchase of perfumes. 250 questionnaires were distributed using convenient sampling technique. 179 properly filled questionnaires were returned forming a response rate of 71.6%.the results of the study revealed that packaging of product was found to have significant impact towards the perception of customers. The four factors of packaging i.e. color, design, material used and text and graphics used were also found to have significant impact on customer perception. Hence all the hypotheses of the study were accepted.